Design and Development of a Solar Power-Based Cocos nucifera Dryer - Sarmiento Jonah C.; Yuga Dickenson M.; Araojo, Ma. Cristina J; Camacho Kate Z.; Tapel Arjay M.; Tumaque Fatima T.; Toyado Dexter M. (Journal of Electronic Design Engineering, 2022)
With the advent of technology, the Solar Power-Based Cocos nucifera Dryer was developed to provide aid among the copra farmers of the Province of Catanduanes, particularly in ensuring that the traditional method of drying, a laborious and time-consuming process could be addressed. Therefore, a better copra quality will then be produced. The Solar Power-Based Cocos nucifera Dryer is a device which makes use of nichrome wire as the heating element. The Arduino microcontroller serves as the brain of the device which controls the heat, temperature, and weight. The Conceive-Develop-Implement-Operate (CDIO) Model was used in the development of the prototype. By transforming the traditional way of drying from sunlight and from kiln to a four-hour drying process with the use of technology, less time and effort are exerted, and better copra quality is to be produced. The findings of the study depict that the project applies to the drying of copra. The components of the project are fully functional and are deemed to be essential to the entire operation. Likewise, the project was also evaluated for its efficiency and was proven to have its potential. Along with the findings of the study, the researchers deemed it is necessary to develop the project to help the copra farmers and entrepreneurs of Catanduanes, Philippines.